2008
DOI: 10.1097/dad.0b013e31817d4c90
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Syringofibroadenoma Associated With Well-Differentiated Squamous Cell Carcinoma

Abstract: We report a case of an eccrine syringofibroadenoma (ESFA) associated with well-differentiated squamous cell carcinoma. The patient was an 85-year-old man, who had a 2.5x2.5-cm, brown-colored ulcerated nodule, with a fragile, flesh-colored bleeding surface located beyond the metacarpophalangeal joint of the second finger of his left hand. Histopathologically, there were areas of a well-differentiated squamous cell carcinoma, alternating with the typical area of ESFA characterized by anastomosing cords, strands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Reactive eccrine syringofibroadenomatosis, which is microscopically characterized by anastomosing thin epithelial strands and cords with ductal structures in a fibrovascular stroma (Fig. ), is likely to reflect another reactive change in the eccrine glands that is believed to represent eccrine gland hyperplasia rather than metaplasia . It has been described in association with several conditions, including SCC, lichen planus, bullous pemphigoid, burns, trauma, and ulcers.…”
Section: Other Changes In Eccrine Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive eccrine syringofibroadenomatosis, which is microscopically characterized by anastomosing thin epithelial strands and cords with ductal structures in a fibrovascular stroma (Fig. ), is likely to reflect another reactive change in the eccrine glands that is believed to represent eccrine gland hyperplasia rather than metaplasia . It has been described in association with several conditions, including SCC, lichen planus, bullous pemphigoid, burns, trauma, and ulcers.…”
Section: Other Changes In Eccrine Glandsmentioning
confidence: 99%
“…6), is likely to reflect another reactive change in the eccrine glands that is believed to represent eccrine gland hyperplasia rather than metaplasia. 10,[42][43][44][45] It has been described in association with several conditions, including SCC, lichen planus, bullous pemphigoid, burns, trauma, and ulcers.…”
Section: Other Changes In Eccrine Glandsmentioning
confidence: 99%
“…4 One study suggested chronic actinic damage to be a cause of the carcinoma associated with ESFA. 19 Overall, the clinical course of reactive ESFA is benign, and the risk of malignant transformation is low. 9 Recurrences and metastasis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…4 One study suggested chronic actinic damage to be a cause of the carcinoma associated with ESFA. 19…”
Section: Discussionmentioning
confidence: 99%
“…ESFA has been associated with squamous cell carcinoma (SCC)[34567] and clear cell acanthoma (CCA) as one of the components in the dual tumor. The occurrence of ESFA with SCC has been more prevalent in literature, and the cases encountered have been summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%